Ordinance no. 4, For the Security of Persons and Property, § 1, GREELEY, ORDINANCES OF THE TOWN (G. A. Webb 1879). - (:unkn) unknown (General Publisher, 1879)
That no person shall fire or discharge any cannon, rifle, gun, pistol or fire arms of any description, or fire, explode or set off any squib, cracker, or anything containing powder, or other combustible or explosive material, in any street, alley or public ground in this town, within one-half mile of the centre of Lincoln Park, without permission of the Board of Trustees, or the written permission of the Mayor of said town, which permission shall limit the time of such firing, and be subject to be revoked at any time after it has been granted...
--
Keywords: DISCHARGE